Cryptococcus neoformans and gattii promote DNA damage in human peripheral blood mononuclear cells - Andrade, Jéssica Cristina Bilizario Noguerol [UNESP]; Gatto, Mariana [UNESP]; Rodrigues, Daniela Ramos [UNESP]; De Campos Soares, Ângela Maria Victoriano [UNESP]; Calvi, Sueli Aparecida [UNESP] (Oxford University Press (OUP), 2018)
Cryptococcosis, a systemic mycosis capable of disseminating to the central nervous system with frequent lethal effects, is caused by the species Cryptococus neoformans and Cryptococcus gattii. Several infectious agents such as virus, bacteria, and parasites may be associated to DNA damage and carcinogenesis in humans. Products of the oxidative metabolism, such as NO, produced as a host defense mechanism to destroy these pathogens, have been implicated in this damage process, due to excessive production related to an established chronic inflammatory response. Here, we investigated whether C. neoformans and/or C. gattii can cause DNA damage in human peripheral blood mononuclear cells (PBMCs) and whether this process is related to NO levels produced by PBMCs. We found that both species are equally able to induce genotoxicity in PBMCs. However, an association between DNA damage and high NO levels was only detected in relation to C. gattii. The results point to the possibility that patients with cryptococcosis are more susceptible to the development of other diseases.
Keywords: Cryptococcus gattii; Cryptococcus neoformans; DNA damage; NO; Peripheral blood mononuclear cells